2013
DOI: 10.1055/s-0038-1623719
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-aided diagnosis of an insulinoma in a cat

Abstract: A 15-year old, neutered female, domestic shorthaired cat was presented for evaluation of a 3-month history of paroxysmal falling over and trembling. In laboratory work the cat displayed a mild hypoglycemia. Ultrasound revealed a nodule in the left pancreatic lobe and surgical excision was performed. The histological diagnosis was an insulinoma. To the authors knowledge this is the first ultrasound description of an insulinoma in a cat. Up to date the cat has a survival time of 32 months without recurrence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…No predilection for age, sex, breed, or body weight was statistically significant in our population. The majority were older domestic cats presenting with neurologic signs (all hypoglycemic and 92.3% had inappropriate serum insulin concentrations), consistent with prior INS case reports 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 and canine INS publications. 10 , 21 , 22 Metastasis was noted as an important factor influencing DFI and DRD.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…No predilection for age, sex, breed, or body weight was statistically significant in our population. The majority were older domestic cats presenting with neurologic signs (all hypoglycemic and 92.3% had inappropriate serum insulin concentrations), consistent with prior INS case reports 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 and canine INS publications. 10 , 21 , 22 Metastasis was noted as an important factor influencing DFI and DRD.…”
Section: Discussionsupporting
confidence: 84%
“…19 All of the previous case reports were cats with stage I disease. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 Similar findings were noted in 2 larger canine studies in which pathologic stage was a predictor of survival time. 10 , 22 The authors of a recent report on the outcome of 48 dogs surgically treated for INS concluded that stage I disease MST was 652 days (range: 2‐1680) and stage II/III disease MST was 320 days (range: 1‐1260).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations